Removing of Crude Oil From Polluted Areas Using the Isolated Fungi From Tehran Oil Refinery. Issue 5 (3rd July 2016) - Mohsenzadeh, Fariba; Shirkhani, Zohreh
ABSTRACT: The pollution of soil and the subsurface environment by crude oil spill and petroleum products spill is a major concern around the world. The aim of this research was to investigate the ability of fungi isolated from Tehran oil refinery area in removing crude oil and to evaluate their enzymatic activities. Plant root samples were collected from the polluted and control areas, and rhizospheral fungi were isolated and determined using the laboratory methods and taxonomic keys. Seven fungal species were isolated and then cultured in potato dextrose agar (PDA) media containing 0–15% (v/v) crude oil. Oil removal was determined after a one-month growth of fungal colonies and then compared with the control media. The results showed that the studied fungi were able to remove crude oil from the media. The highest removal efficiency was observed in Aspergillus sp. Total protein content and enzymatic activity (of peroxidase and catalase) increased with increasing crude oil pollution. The highest enzymatic activity was evaluated in Aspergillus sp. growing in media containing 15% petroleum and the lowest activity was found in non-polluted groups. Results showed that there is a direct correlation between oil-removing potency and enzymatic activity. Aspergillus sp. showed the highest enzyme activity and also the highest petroleum removal efficiency.